PM2.5 Temporal Pattern in Jambi City: Meteorological Drivers and Air Mass Trajectory Analysis - Benedy Fajar; Muhammad Damris; Kemas Rahmat Saleh Wiharja; Elma Mutmainnah; Noorlin Mohamad; Rizki Andre Handika (Universitas Diponegoro, 2026)
Air pollution, particularly particles with a diameter of less or equal than 2.5 micrometers (PM2.5), has become an important global health and environmental problem. Jambi City in Sumatra is highly susceptible to this issue, both locally and particularly influenced by forest fires. As early studies were conducted over a short period, this study examined the meteorological factors that influenced PM2.5 levels and estimated the pollutant transport pathways over two years in the post-COVID-19 period (2023-2024). The methods employed were time-series analysis, scatter-plot evaluation, multiple linear regression analysis, and backward trajectory modeling using HYSPLIT. The results show that the average PM2.5 concentration in 2023 (30.53 µg/m³) was higher than in 2024 (25.36 µg/m³), with night-time levels generally exceeding day-time levels. 3.69% of the days exceeded Indonesia’s daily air quality standard, while 90.83% surpassed the stricter WHO guideline. Meteorological factors explained only 23–38% of PM2.5, with temperature positively correlated, wind speed showing mixed effects, and humidity and rainfall negatively correlated.. The major PM₂.₅ sources influenced by the southeast–South Sumatra, particularly South Sumatra, highlighting the strong stimulus of transboundary emissions alongside local sources. In the future, studies focusing on chemistry-based source apportionment are needed to accurately separate each contributing source.